Neuroeconomics - Houser, Daniel; McCabe, Kevin (Advances in health economics and health services research, 2008)
The purpose of the series Advances in Health Economics and Health Services Research is to consider all topics in health economics and the related field of health services research. Each volume is devoted to a specific topic. Most volumes consist of between ten and twelve papers, but a few may take the form of monographs by one or more authors. All areas in the field are covered including the production of and demand for health; the demand for medical care services; the financing of these services; the markets for physicians, nurses, dentists, hospitals, and drugs; the economics of substance use; health in developing countries; and, the economics of medical technology. The series is a forum for theoretical and empirical research. The latter employ data both for developing and developed countries. While most studies focus on economic issues, contributions from other social scientists are welcomed.